2020
DOI: 10.11591/ijere.v9i2.20467
|View full text |Cite
|
Sign up to set email alerts
|

Stationenlernen learning techniques and German language learning outcomes

Abstract: This quasi-experimental study was conducted with the aim of obtaining a clear picture of the presence of influence of the application of Stationenlernen learning techniques to the learning outcomes of German students. The study population was all of these students, while the selected sample was 11th grade students. Data collection techniques used in this study are: (1) observation and interviews, (2) the implementation of pre-test (3) the implementation of experiments, and (4) the implementation of post-test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Then the sections are grouped, tabulated, and described about the original idea. The data source for this research is the scientific journal article by Litualy and Serpara [12]. In general, the purpose of this article is to determine if the use of the Stationenlernen learning strategy improves German learning results.…”
Section: Methodsmentioning
confidence: 99%
“…Then the sections are grouped, tabulated, and described about the original idea. The data source for this research is the scientific journal article by Litualy and Serpara [12]. In general, the purpose of this article is to determine if the use of the Stationenlernen learning strategy improves German learning results.…”
Section: Methodsmentioning
confidence: 99%
“…The data analysis results indicated that, following the teaching intervention, students in the experimental group exhibited significantly better performance in evidence and refutation compared to the control group. Litualy & Serpara (2020) conducted an analysis of static learning skills, German language learning effects, and the outcomes of German students using SOLO, employing observation and interviews ( Litualy & Serpara, 2020 ). The findings demonstrated that accurate and reliable calculation results could be derived through the computation and analysis of the obtained data.…”
Section: Recent Related Workmentioning
confidence: 99%
“…Dengan penguasaan bahasa Jerman secara baik para mahasiswa dapat terbantu untuk memperluas wawasan berpikir mereka dan sekaligus meningkatkan pengetahuan mereka . Terdapat lima manfaat mengapa belajar Bahasa Jerman itu penting (Birgit Gasperschitz, Susanne Hecht, und Giuseppina Piccardo, (2007: i) dalam (Litualy & Serpara, 2020): (1) Bahasa Jerman: bahasa yang penting untuk perdagangan, sebab Jerman merupakan negara pengekspor utama di dunia, karena memiliki ekonomi yang kuat dan partner industri-perdagangan paling penting bagi Indonesia di Uni Eropa. Dalam 10 tahun terakhir, bahasa Jerman menjadi linguafranca regional di negara-negara eropa tengah dan timur.…”
Section: Pendahuluanunclassified